(untitled) (Revista da Escola de Guerra Naval, 2023)
The world is struggling with the widely spread effects of the virus Covid-19. The damage until now took more than a million people in less than a year, which is more than a considerably number of small wars together. The purpose of this article is to identify signs, uncertainties and trends from future studies that have been written in the last few months by government agencies, large private companies, academic institutions and worldwide organizations about the influence of the pandemic in areas such as economy, international relations, geopolitics, environment, technology and society in order to assess those of main potential impacts for national defense and international security. The methodology relied on semantic analysis application based on 55 selected futures studies (reports, papers, books etc.) written in three largely spoken languages regarding both Covid-19 and prospective scenarios. The analysis focus on the complex tangle between technology and society, as well as, between politics and economy. The results are summarized in a list of variables of trend or uncertainties followed by some possible impacts on how they can interact or affect the issue. This paper points out the necessity to look over this pandemic horizon with contributions from different government departments, think tanks, academics and non- governmental organizations to short the time-lapse between the strategic formulation and its results.